Technology and Noble Traditions in Pesantren - Ahmad Khuza'i Faruq; Hepni Hepni; Sujiwo Sujiwo (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
One of the Islamic educational institutions that has a high existence throughout the history of the nation's civilization to date is Pesantren. As indigenous religious education institutions, Pesantren have a significant contribution in creating a generation that has good ethics and etiquette (akhlakul karimah). Pesantren has a noble tradition which is a unique characteristic inherent in it, such as Sufism, ubudiyah, scientific rihlah, book study, thoriqoh practice, and other socio-religious activities. Another unique character that is a special characteristic of pesantren is the use of the yellow book as a literature study with a special method of learning. The development of science and technology as well as the swift currents of modernization pose a major challenge to Pesantren. The convenience that technology brings is in contrast to the character education applied to Pesantren. Pesantren are required to open themselves to changing times so that they are not overshadowed by being left behind, but the obligation to preserve the noble values that have become traditions must be maintained. In this study the authors used a qualitative descriptive method, the data sources were obtained from primary and secondary data. Data collection techniques from literature studies, observations, interviews, and documentation at a number of Pesantren in East Java in terms of the application of technology to support the life of pesantren and its relation to the preservation of the noble traditions that exist in pesantren. Technology can function as a tool to help the life of the pesantren, such as in administration, learning processes and other activities within the pesantren. The application of appropriate, proportional and not excessive technology can help simplify the life of the pesantren without having to diminish the noble values in the pesantren which were passed down by the previous ulama' sacredly.